Remote Sensing and Geographical Information System to Identify Drought Potency - Raharjo, Puguh Dwi (Makara Journal of Technology, 2010)
Remote Sensing and Geographical Information System to Identify Drought Potency. Kebumen regency was drought in year 2008, community clean water shortages and irrigation water following a decline in water resources. The use of remote sensing data and GIS can be used to identify the potential for drought-prone areas. Transformation of Landsat TM satellite imagery to obtain the brightness index, wetness index and vegetation index used to determine surface conditions in relation to drought. Brightness index and wetness index derived from the tasseled cap modifications, while the vegetation index derived from normalized difference vegetation index (NDVI) values. Other parameters such as aquifer conditions, rainfall and other types of dry agricultural land use was a factor in identifying drought. The data are performed in accordance with the zone description in order to get the study area in relation to regional drought. The result of the research is identified area the district of Karangsambung, Karanggayam, Sadang, Alian, Puring, Klirong, Buluspesantren, Ambal and Mirit potential drought.